Temperature Influence on the Optical Properties, Attenuation Coefficient, and Total Molecular Cross Section of Dhunge Dhara Drinking Water - Dhobi, Saddam Husain; Koirala, Bibek; Yadav, Kishori; Nakarmi, Jeevan Jyoti; Gupta, Suresh Prasad; Das, Santosh Kumar; Shah, Arun Kumar; Paudel, Kuldip; Dahal, Kushal; Sah, Ram Lal (UI Scholars Hub, 2022)
This work aims to measure the different parameters of Dhunge Dhara water (DDW) such as absorbance, transmittance, mass attenuation coefficient (MAC), and molecular cross section (MCS) and experimentally compare the obtained values with those of pure water (PW) at various temperatures (5 °C to 90 °C) using a theremino spectrometer. Observation shows that the parameters vary with temperature and wavelength. The transmittance of DDW ranges from 18% to 85% and absorbance of the same ranges from 0.09 Au to 0.7 Au. Meanwhile, the transmittance of PW ranges from 40% to 98% and the absorbance of the same ranges from 0.09 Au to 0.39 Au. The MAC of PW ranges from 0.02 cm2g−1 to 0.6 cm2g−1, and that for DDW ranges from 0.2 cm2g−1 to 1.1 cm2g−1 at 30 °C. The MCS of PW ranges from to , and that of DDW ranges from to at 30 °C. In conclusion, DDW has an extremely high amount of impurities and total dissolved solids and is recommended to be filtered prior to use (drinking and cooking)